2D simulation of the initial stage of the beam-plasma discharge - Dadyka, D.I.; Anisimov, I.O. (Вопросы атомной науки и техники, 2015)
2D electrostatic PIC code for simulation of the initial stage of the beam-plasma discharge in the rectangular geometry is developed. Simulation results for discharge in helium are presented. It is shown that the area of the most intensive plasma heating eventually moves further from the injector. In this area the intensive ionization takes place.